Nickel-based electrocatalyst as well as preparation method and application thereof

By modifying the nickel-based electrocatalysts with multi-layer structure, the problem of high and unstable kinetic barriers during the water cracking process of the existing nickel sulfide electrocatalysts is solved, and the hydrogen production effect of alkali water cracking with high efficiency and low energy consumption is achieved.

CN119877025APending Publication Date: 2025-04-25HYDROGEN REALM (BEIJING) NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311373635.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

During the water cracking process, the existing nickel sulfide electrocatalyst has a high kinetic barrier, limited active center, and unstable catalyst, resulting in high tank voltage and large energy consumption.

Method used

By pre-sulfurizing, vulcanizing, sulfonating and polymerizing the nickel-based substrate material, a multi-layer structure of a nickel-based electrocatalyst is formed, including a nickel-based substrate, a vulcanizing layer, a sulfonating layer and a capping layer, enhancing the electrocatalytic performance of the catalyst.

Benefits of technology

While ensuring efficient hydrogen production, it is achieved to significantly reduce the tank voltage of the alkaline water cracking hydrogen production reaction, improve the stability and electrocatalytic efficiency of the catalyst, and reduce energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877025A_ABST
    Figure CN119877025A_ABST
Patent Text Reader

Abstract

The invention provides a nickel-based electrocatalyst as well as a preparation method and application thereof, and relates to the technical field of alkaline water electrolysis. Specifically, the nickel-based electrocatalyst comprises a nickel substrate, a vulcanization layer, a sulfonation layer and an end sealing layer from inside to outside, wherein the sulfonation layer comprises a sulfonic acid group, and the end-capping layer comprises at least one of anilino, pyrrolyl or thienyl. A nickel-based metal raw material is sequentially subjected to pre-vulcanization, vulcanization, sulfonation and end capping, and the enhanced nickel-based electro-catalytic material with sulfonation groups fixed on the surface and end capped by a polymer is obtained. The nickel-based electrocatalyst disclosed by the invention has extremely high stability while ensuring that the catalytic efficiency of electrolyzed alkaline water is improved, the cost is low, and the preparation method is simple and easy to implement; when the catalyst is applied to an alkaline water splitting hydrogen production process, the cell voltage can be remarkably reduced, the problem of high energy consumption is solved, and the catalyst has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of alkaline water electrolysis, and in particular to a nickel-based electrocatalyst and a preparation method and application thereof. Background Art

[0002] At present, the energy field is widely committed to the development and utilization of clean energy such as solar energy, wind energy, biomass energy, geothermal energy, and hydrogen energy. Hydrogen is an element with abundant reserves on the earth. It has the advantages of environmental friendliness and high calorific value. It is imperative to actively explore the development and utilization of "green" hydrogen fuel. Among various hydrogen production methods, water electrolysis is an efficient, environmentally friendly and convenient method to produce "green hydrogen". During the water splitting process, the cathode of the electrolyzer undergoes a hydrogen reduction reaction and generates hydrogen (also known as the hydrogen evolution reaction; HER), and the anode undergoes an oxygen oxidation reaction and generates oxygen (also known as the oxygen evolution reaction, OER).

[0003] However, the oxygen evolution process at the anode involves a four-electron reaction, which is a kinetically slow process. For this reason, in industrial production, the cell voltage is often used to increase the speed of the anode process, thereby improving the electrolysis efficiency. The resulting excessive energy consumption has always been the main problem faced by the water splitting hydrogen production industry. At present, the electrolytic hydrogen production methods that have been used for large-scale industrial production include the proton exchange membrane method and the alkaline water splitting method. Among them, the anode and cathode catalysts required for the proton exchange membrane method are precious metal materials such as platinum, rhodium, and iridium, so the source of the catalyst raw materials is scarce and the cost is high. The anode and cathode catalysts used in alkaline water splitting hydrogen production are mostly nickel-based materials. As we all know, nickel is a non-precious metal material with low price, easy raw materials, and stable properties, so the alkaline water splitting method is still the most widely used method in the current large-scale water electrolysis hydrogen production industry. However, the catalytic activity of metal nickel for water splitting is limited by its inherent properties, so the development of high-activity, high-stability, and low-cost catalysts is still a research hotspot and an urgent problem to be solved in the field of alkaline water splitting to prepare "green hydrogen".

[0004] By adopting some physical and chemical methods, nickel can be compounded with other metals or non-metals to form a nickel-based material composed of multiple components. Then, through the synergistic effect between the components and the regulation of the microstructure and morphology of the materials, the stability and electrocatalytic efficiency of these materials can be significantly improved. Among the many types of nickel-based catalytic materials, nickel sulfide effectively promotes the transmission of electrons due to its hexagonal lattice structure and the grid connection method formed between nickel, so that it exhibits multifunctional catalytic properties. However, when using nickel sulfide for electrocatalytic water splitting, its kinetic barrier is still high, the number of active centers and high-order ions is limited, and the catalyst molecules are easy to diffuse and lose, which often leads to problems such as high actual cell voltage, high energy consumption, and unstable catalysts. The existing technology uses a variety of means such as morphology engineering, crystal phase control, element doping, material composite, and optimized synthesis method to further improve the electrocatalytic performance of the catalyst, but there are few technologies that essentially change the activity and stability of the electrocatalyst to improve the overall performance of the electrocatalytic material.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The first purpose of the present invention is to provide a nickel-based electrocatalyst to solve the technical problem that nickel sulfide electrocatalysts cannot simultaneously ensure the activity and stability of the electrocatalyst; the nickel-based electrocatalyst of the present invention can effectively reduce the cell voltage of the alkaline water cracking hydrogen production reaction and effectively improve the efficiency of the hydrogen production reaction.

[0007] The second object of the present invention is to provide a method for preparing the nickel-based electrocatalyst, which has cheap and readily available raw materials, a simple production process, does not require expensive equipment and harsh production conditions, and is suitable for large-scale industrial production.

[0008] The third object of the present invention is to provide a water electrolysis electrode, comprising the nickel-based electrocatalyst.

[0009] The fourth object of the present invention is to provide a method for electrolyzing water, comprising the water electrolysis electrode.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0011] A nickel-based electrocatalyst comprises, from inside to outside, a nickel substrate, a sulfide layer, a sulfonate layer and a capping layer;

[0012] The sulfonation layer includes an organic sulfonic acid group, and the end-capping layer includes at least one of an aniline group, a pyrrolyl group or a thiophene group.

[0013] The method for preparing the nickel-based electrocatalyst comprises the following steps:

[0014] Step 1, preparation of sulfonation layer: placing the nickel substrate in a sulfur-containing alkaline solution for pre-sulfurization, and then adding nickel sulfate and a dispersant for sealing reaction to obtain a sulfided nickel substrate; fully mixing the sulfided nickel substrate with a sulfonation reagent, and after reaction, obtaining a nickel substrate with a sulfonation layer on the surface;

[0015] Step 2, preparation of the end-capping layer: the nickel substrate with the sulfonated layer on the surface is fully mixed with the end-capping agent and the oxidative polymerization agent in sequence, and after the reaction, a nickel-based electrocatalyst with the end-capping layer fixed on the surface is obtained.

[0016] A water electrolysis electrode comprises the nickel-based electrocatalyst.

[0017] A method for electrolyzing water, using electrodes connected to a power source to electrolyze an electrolyte, wherein the electrodes include the water electrolysis electrodes, and the electrolyte is an alkaline aqueous solution.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention provides a nickel-based electrocatalyst and a supporting preparation method thereof. By sequentially pre-sulfurizing, sulfurizing, sulfonating and polymerizing a nickel substrate material, an enhanced nickel-based electrocatalyst having sulfonated groups fixed on the surface and capped by a polymer is obtained. The nickel-based electrocatalyst of the present invention can achieve extremely high stability while ensuring improved efficiency of hydrogen production by alkaline water electrolysis, and has low cost and a simple preparation method. When applied to an alkaline water splitting hydrogen production process, the cell voltage can be significantly reduced, thereby solving the problem of high energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the specific implementation of the present invention or the technical solution in the prior art, the following briefly introduces the drawings required for use in the specific implementation or the prior art description. Obviously, the drawings described below are some implementations of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0021] Figure 1 Provides a SEM image of the nickel-based electrocatalyst prepared in Example 1 of the present invention;

[0022] Figure 2 The FT-IR spectrum of the nickel-based electrocatalyst prepared in Example 1 of the present invention is provided;

[0023] Figure 3 Provides a linear sweep voltammetric curve obtained in Experimental Example 1 of the present invention;

[0024] Figure 4 The current density-time curve obtained in Experimental Example 2 of the present invention is provided. DETAILED DESCRIPTION

[0025] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0026] The first aspect of the present invention is to provide a nickel-based electrocatalyst, which includes a nickel substrate, a sulfide layer, a sulfonation layer and a capping layer from the inside to the outside; wherein the sulfonation layer includes a sulfonic acid group, and the capping layer includes at least one of an aniline group, a pyrrolyl group or a thiophene group.

[0027] The end-capping layer used in the present invention can achieve the end-capping of the lipophilic end of the sulfonic acid group, and the end-capping layer may include polymers such as polyaniline, polypyrrole, polythiophene, aniline-pyrrole copolymer, aniline-thiophene copolymer, pyrrole-thiophene copolymer, etc. It should be noted that the end-capping layer also includes any conventional functional group structure, such as hydroxyl, ester, alkyl, alkoxy, etc., but as a preferred embodiment, the group that bears the end-capping function in the end-capping layer is composed of at least one of an aniline group, a pyrrole group or a thiophene group.

[0028] The present invention sequentially sulfurizes, sulfonates and caps the nickel-based surface, thereby improving the overall performance of the electrocatalyst to prevent the nickel-based material from weakening or losing its electrocatalytic effect due to an unexpected force reacting with the sulfurized layer.

[0029] In the structure of each layer of the nickel-based electrocatalyst of the present invention: compared with the pure nickel surface, the sulfided nickel is conducive to the coating of the hydrophilic end of the sulfonic acid and the formation of a sulfonated layer. The hydrophobic end in the sulfonated layer is easy to adsorb the end-capping molecules. Furthermore, the end-capping molecules are polymerized under the initiation of the oxidant, thereby forming an end-capping layer on the surface, and the loose and porous end-capping layer is not only conducive to the passage of reactant molecules and prevents the concentration of nickel ions generated on the nickel-based surface during the electrode reaction from decreasing due to diffusion, but also its conjugated structure provides a channel for charge transfer. Therefore, compared with the sulfided nickel-based electrocatalyst, the present invention significantly enhances the electrocatalytic effect of the material through the modification of the sulfonated layer and the end-capping layer.

[0030] The present invention can use any form of pure nickel or high nickel content material as the nickel substrate. As a preferred embodiment, the nickel substrate includes at least one of a nickel sheet, a nickel alloy sheet, a nickel foam or a nickel wire mesh; wherein the nickel alloy sheet may contain any one or more elements such as chromium, tungsten, cobalt, copper, molybdenum, iron, zinc, titanium, vanadium, manganese, aluminum, carbon, etc.; the nickel content in the nickel substrate is ≥95%.

[0031] The second aspect of the present invention is to provide a method for preparing the nickel-based electrocatalyst, which mainly includes the following two steps, which correspond to the preparation of the sulfonation layer and the end-capping layer described in the first aspect, respectively.

[0032] Step 1, preparation of sulfonation layer: placing the nickel substrate in a sulfur-containing alkaline solution for pre-sulfurization, and then adding nickel sulfate and a dispersant for sealing reaction to obtain a sulfided nickel substrate; fully mixing the sulfided nickel substrate with a sulfonation reagent, and after reaction, obtaining a nickel substrate with a sulfonation layer on the surface;

[0033] This step mainly includes the following reaction processes: s1, pre-immersing the nickel substrate in a sulfur-containing alkaline solution for pre-sulfurization to ensure sufficient contact between the sulfur and the nickel substrate; s2, adding nickel sulfate and a dispersant to achieve a reaction between the nickel sulfate and sulfur to generate nickel sulfide, thereby obtaining a surface-sulfurized nickel substrate; s3, the positively charged nickel on the surface of the sulfide layer of the nickel substrate combines with the sulfonic acid anion of the sulfonation reagent to obtain a surface-sulfonated nickel substrate.

[0034] Step 2, preparation of the end-capping layer: the nickel substrate with the sulfonated layer on the surface is fully mixed with the end-capping agent and the oxidative polymerization agent in sequence, and after the reaction, a nickel-based electrocatalyst with the sulfonated layer fixed on the surface with the end-capping layer is obtained;

[0035] This step mainly includes the following reaction processes: s1, the surface sulfonated nickel substrate is first mixed with the capping reagent; the sulfonation reagent used in the previous step has both lipophilic and hydrophilic characteristics, the hydrophilic end is combined with the sulfide layer on the surface of the nickel substrate, and the lipophilic end is combined with the capping reagent; s2, by using an oxidative polymerization reagent to initiate the polymerization of the capping reagent on the capping side, the sulfonation layer on the surface of the nickel substrate is fixed, thereby significantly improving the electrocatalytic activity and stability of the nickel-based material.

[0036] As a preferred embodiment, the sulfur-containing alkali solution comprises sulfur powder and alkali solution, and the solid-liquid ratio of the sulfur powder to the alkali solution is 1g: (20-40)mL; as an optional embodiment, the solid-liquid ratio of the sulfur powder to the alkali solution includes but is not limited to any ratio of 1g: 20mL, 1g: 22mL, 1g: 25mL, 1g: 28mL, 1g: 30mL, 1g: 32mL, 1g: 35mL, 1g: 38mL, 1g: 40mL, or a range value composed of any two ratios.

[0037] As a preferred embodiment, the pH of the alkali solution is ≥10; as a more preferred embodiment, the alkali solution can be an alkaline aqueous solution such as a sodium hydroxide solution, a potassium hydroxide solution, etc.; as a further preferred embodiment, those skilled in the art can adjust the concentration or content of the solute in the alkali solution according to the difference in application scenarios; for example, in a laboratory or small-scale production, the alkali solution uses a 0.5 mol / L to 2 mol / L potassium hydroxide solution; or, in some large-scale batch application scenarios, the alkali solution uses a 0.03% to 30% potassium hydroxide solution.

[0038] As a preferred embodiment, the pre-vulcanization time is 0.2h to 1h; as an optional embodiment, the pre-vulcanization time includes but is not limited to any point value among 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1 (h) or a range value consisting of any two point values.

[0039] As a preferred embodiment, the dispersant includes at least one of polyvinyl pyrrolidone, polyvinyl alcohol, methyl cellulose and carboxymethyl cellulose.

[0040] As a preferred embodiment, the mass ratio of the nickel sulfate to the dispersant is 1:(0.5-1.5); as an optional embodiment, the mass ratio of the nickel sulfate to the dispersant includes but is not limited to any ratio of 1:0.5, 1:0.6, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5 or a range value consisting of any two ratios.

[0041] As a preferred embodiment, the nickel sulfate and the dispersant are dissolved in a first solvent, and then the pre-sulfurized nickel substrate is added to perform a sealing reaction; wherein the first solvent includes water and polyethylene glycol; as a more preferred embodiment, the first solvent is water and polyethylene glycol, the volume ratio of the two is 2:1, and the molecular weight of the polyethylene glycol is 200-600; as a more preferred embodiment, the ratio of the added amount of the sulfate and the first solvent is 1: (100-200) g / mL.

[0042] As a preferred embodiment, the temperature of the sealing reaction is 140°C to 180°C, and the time of the sealing reaction is 5h to 20h; as an optional embodiment, the temperature of the sealing reaction includes but is not limited to any point value among 140, 142, 144, 145, 146, 148, 150, 152, 155, 158, 160, 162, 164, 165, 166, 168, 170, 172, 175, 178, 180 (°C) or a range value consisting of any two point values, and the time of the sealing reaction includes but is not limited to any point value among 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 (h) or a range value consisting of any two point values.

[0043] As a preferred embodiment, the sulfurized nickel substrate is further washed after the sealing reaction; specifically, the steps include: sequentially immersing the sulfurized nickel sheet in acetone and anhydrous ethanol, and naturally drying to obtain a surface-sulfurized nickel sheet.

[0044] As a preferred embodiment, the sulfonating agent is an organic sulfonic acid or an organic sulfonate; specifically, the sulfonating agent includes at least one of p-toluenesulfonic acid, p-ethylbenzenesulfonic acid, dodecylsulfonic acid, dodecylbenzenesulfonic acid, sodium methylbenzenesulfonate, sodium p-ethylbenzenesulfonate, sodium dodecylsulfonate, sodium dodecylbenzenesulfonate, potassium p-toluenesulfonate, potassium p-ethylbenzenesulfonate, potassium dodecylsulfonate or potassium dodecylbenzenesulfonate.

[0045] As a preferred embodiment, based on the amount of sulfonic acid group, per 1m 2 The amount of the sulfonating agent used for the sulfided nickel substrate is 0.05 mmol to 0.15 mmol.

[0046] As a preferred embodiment, the sulfided nickel substrate and the sulfonated reagent are fully mixed in a second solvent; wherein the second solvent comprises ethanol and deionized water, and the volume ratio of the ethanol to the deionized water is 1:(3-5); as a more preferred embodiment, the ratio of the added amount of the sulfonated reagent to the second solvent is 1:(15-30) mmol / mL.

[0047] As a preferred embodiment, the step of fully mixing and reacting the sulfided nickel substrate and the sulfonation reagent is carried out in an ice water bath and under stirring.

[0048] As a preferred embodiment, the time for the mixed reaction of the sulfonating reagent and the sulfided nickel substrate is 0.2h to 1h; as an optional embodiment, the time for the mixed reaction of the sulfonating reagent and the sulfided nickel substrate includes but is not limited to any point value among 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1 (h) or a range value consisting of any two point values.

[0049] As a preferred embodiment, the capping agent includes at least one of aniline, pyrrole or thiophene.

[0050] As a preferred embodiment, the molar ratio of the end-capping agent to the sulfonating agent is (1-4):1; as an optional embodiment, the molar ratio of the end-capping agent to the sulfonating agent includes but is not limited to any point value among 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1 or a ratio range consisting of any two point values.

[0051] As a preferred embodiment, the mixing reaction is carried out for 0.2h to 1h after adding the capping agent, and then the oxidative polymerization agent is added; as an optional embodiment, the mixing reaction time after adding the capping agent includes but is not limited to any point value among 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1 (h) or a range value consisting of any two point values.

[0052] As a preferred embodiment, the oxidative polymerization agent includes at least one of ammonium persulfate, ferric chloride, chloroplatinic acid or hydrogen peroxide.

[0053] As a preferred embodiment, the molar ratio of the oxidative polymerization reagent to the end-capping reagent is (0.5-2):1; as an optional embodiment, the molar ratio of the oxidative polymerization reagent to the end-capping reagent includes but is not limited to any point value among 0.5:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.8:1, 2:1, or a ratio range consisting of any two point values.

[0054] As a preferred embodiment, the oxidative polymerization reagent is added and mixed for reaction for 1h to 10h to obtain the nickel-based electrocatalyst; as a preferred embodiment, the time for the mixed reaction after adding the oxidative polymerization reagent includes but is not limited to any point value among 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 7, 8, 9, 9.5, 10 (h) or a range value consisting of any two point values.

[0055] As a preferred embodiment, after the mixing reaction with the oxidative polymerization reagent is completed, the nickel-based electrocatalyst is further washed; specifically, the following steps are included: immersing in acetone and anhydrous ethanol in sequence, and then drying at 60° C. to obtain the nickel-based electrocatalyst.

[0056] As a preferred embodiment, in step 2, the end-capping reagent and the oxidative polymerization reagent can be directly added to the mixed solution obtained after the reaction in step 1 in sequence; in terms of volume, the mixed solution obtained after the reaction in step 1 and the second solvent have a similar volume, so the present invention also provides an additional method for measuring the amount of the end-capping reagent and the oxidative polymerization reagent added by the volume of the second solvent. Specifically, the volume ratio of the end-capping reagent to the second solvent is 1: (60-120), and the ratio of the mass of the oxidative polymerization reagent to the volume of the second solvent is 1: (20-40) g / mL.

[0057] The third aspect of the present invention is to provide a water electrolysis electrode, comprising the nickel-based electrocatalyst described in the first aspect.

[0058] The water electrolysis electrode can be independently prepared by using the nickel-based electrocatalyst; after the nickel-based electrocatalyst is processed by one or more of the methods of cleaning, surface treatment, mechanical processing, activation, etc., an electrode for water electrolysis is obtained.

[0059] The water electrolysis electrode may also include the nickel-based electrocatalyst and other materials, that is, those skilled in the art can select any feasible material to be compounded with the nickel-based electrocatalyst and serve together as the water electrolysis electrode.

[0060] The water electrolysis electrode including the nickel-based electrocatalyst can be used alone as the positive electrode or negative electrode of the water electrolysis device, in which case other optional negative electrodes or positive electrodes can be used in combination with it; it can also be used as both the positive electrode and the negative electrode of the water electrolysis device.

[0061] The fourth aspect of the present invention is to provide a method for electrolyzing water, using electrodes connected to a power source to electrolyze an electrolyte, wherein the electrodes include the water electrolysis electrodes described in the third aspect, and the electrolyte is an alkaline aqueous solution.

[0062] As a preferred embodiment, the alkaline aqueous solution includes one or both of sodium hydroxide solution and potassium hydroxide solution.

[0063] As a more preferred embodiment, the mass concentration of the alkaline solute in the alkaline aqueous solution is 10% to 30%; correspondingly, when potassium hydroxide solution is used as the electrolyte, the mass concentration of the potassium hydroxide solution is 10% to 30%; when a mixed solution of sodium hydroxide and potassium hydroxide is used, the sum of the mass concentrations of sodium hydroxide and potassium hydroxide is 10% to 30%.

[0064] As a preferred embodiment, the voltage of the power supply is a constant voltage or an alternating voltage; it has been found through testing that the OER process reaches 10 mA cm -2 The voltage required for the current density is as low as 1.41V.

[0065] Example 1

[0066] (1) In reactor No. 1, add 0.5 g of sulfur powder to 15 mL of 0.75 mol L -1 The nickel foam is immersed in a NaOH solution and pre-sulfurized for 0.75 h under stirring conditions.

[0067] (2) In reactor No. 2, add 25 mL of a mixed solution of water and polyethylene glycol (molecular weight 400) in a volume ratio of 2:1, add 0.65 g of nickel sulfate and 0.5 g of polyvinyl pyrrolidone under stirring conditions; and add the solution in reactor No. 2 to reactor No. 1 under rapid and continuous stirring conditions.

[0068] (3) All the solution in reactor No. 1 and the nickel foam therein were transferred to a stainless steel high-pressure reactor lined with polytetrafluoroethylene and sealed, reacted at 150° C. for 15 h, and after cooling, the nickel foam was taken out, washed with acetone and anhydrous ethanol in turn, and dried naturally to obtain the nickel foam.

[0069] (4) The nickel foam is placed in a mixed solution of 0.65 g of sodium p-toluenesulfonate and 100 mL of anhydrous ethanol and deionized water in a volume ratio of 1:4, and placed in an ice water bath, and rapidly and continuously stirred for 0.75 h to achieve re-sulfonation of the surface of the nickel foam after sulfidation.

[0070] (5) Under ice-water bath conditions, 1.0 mL of aniline was added to the sulfonation solution and stirred for 0.75 h to achieve the end-capping of the hydrophobic end of the sulfonation group on the surface of the nickel foam; 10 mL of 0.65 mol / L ammonium persulfate aqueous solution was added to the solution under rapid stirring conditions, and rapid stirring was continued for 10 min. Then, stirring was stopped and allowed to stand for 8 h. Then, the nickel foam was taken out, washed with acetone and anhydrous ethanol in turn, and dried at 60° C. for 2 h to prepare the surface sulfonation-enhanced nickel-based electrocatalyst of this embodiment.

[0071] The nickel-based electrocatalyst prepared in this example was placed in a scanning electron microscope sample chamber to observe its surface morphology. Figure 1 As shown. Figure 1It can be seen that the surface of the material is evenly and tightly covered with circular protrusions with a diameter of 100nm to 200nm, indicating that the sulfurization effect in the preparation process has a significant etching effect on the surface of the nickel foam; the surface of these circular protrusions is coated with fibrous materials, indicating that the organic small molecules used for end-capping are successfully coated on the surface of the nickel base material after polymerization.

[0072] The powder on the surface of the nickel-based electrocatalyst prepared in this example was scraped and placed in an agate mortar, mixed with potassium bromide crystals, ground and pressed into thin sheets, and then subjected to FT-IR spectrum testing using an infrared spectrometer with a scanning range of 400 cm -1 ~3000cm -1 , the test results are as follows Figure 2 As shown. Figure 2 It can be seen that at 480cm -1 The absorption band at 696 cm-1 corresponds to the Ni-S stretching vibration, indicating that the surface of nickel foam has been sulfurized. -1 、1047cm -1 、1364cm -1 The typical vibration absorption of -S=O proves that the sulfonated groups on the surface of nickel foam are fixed; -1 、1299cm -1 and 1495cm -1 、1587cm -1 The absorption bands near the 613cm-1 aniline molecule correspond to the CN stretching vibration of the aniline molecule and the C=C stretching vibration of the benzene ring, indicating that the small molecule aniline used for end-capping has polymerized on the surface of the electrocatalyst. The aniline polymerization product has the characteristics of being insoluble and corrosion-resistant, which is beneficial to the fixation of the sulfonated groups on the surface of the nickel substrate. In addition, the 613cm-1 aniline -1 The absorption band corresponds to the out-of-plane bending vibration of CH in organic molecules, located at 819 cm -1 and 1105cm -1 The absorption bands correspond to the CC stretching vibration and CO stretching vibration of the residual PEG in the material.

[0073] Example 2

[0074] It is basically the same as Example 1, except that:

[0075] In step (1): the volume of the NaOH solution is 10 mL, and the presulfurization time is 1 h.

[0076] Example 3

[0077] It is basically the same as Example 1, except that:

[0078] In step (1): the volume of the NaOH solution is 20 mL, and the presulfurization time is 0.5 h.

[0079] Example 4

[0080] It is basically the same as Example 1, except that:

[0081] In step (2): the mass of polyvinyl pyrrolidone is 0.65 g.

[0082] Example 5

[0083] It is basically the same as Example 1, except that:

[0084] In step (3): after sealing, react at 140° C. for 20 h.

[0085] Example 6

[0086] It is basically the same as Example 1, except that:

[0087] In step (3): after sealing, react at 160° C. for 10 h.

[0088] Example 7

[0089] It is basically the same as Example 1, except that:

[0090] In step (2): polyvinyl pyrrolidone is replaced by methyl cellulose;

[0091] In step (4): 0.65 g of sodium p-toluenesulfonate was replaced with 1.09 g of dodecylbenzenesulfonic acid;

[0092] In step (5): 1.0 mL of aniline was replaced with 0.87 mL of thiophene, and 0.65 mol / L of aqueous ammonium persulfate solution was replaced with 1.3 mol / L of aqueous ferric chloride solution.

[0093] Example 8

[0094] It is basically the same as Example 1, except that:

[0095] In step (2): polyvinyl pyrrolidone is replaced by methyl cellulose;

[0096] In step (4): 0.65 g of sodium p-toluenesulfonate was replaced with 1.22 g of potassium dodecylbenzenesulfonate;

[0097] In step (5): 1.0 mL of aniline was replaced with 0.76 mL of pyrrole, and 0.65 mol / L of aqueous ammonium persulfate solution was replaced with 0.33 mol / L of aqueous chloroplatinic acid solution.

[0098] Example 9

[0099] It is basically the same as Example 1, except that:

[0100] In step (4): 0.65 g of sodium p-toluenesulfonate was replaced with 0.57 g of p-toluenesulfonic acid;

[0101] In step (5): 10 mL of 0.65 mol / L ammonium persulfate aqueous solution is replaced with 5 mL of 4.5% hydrogen peroxide.

[0102] Comparative Example 1

[0103] The method is basically the same as Example 1, except that steps (1) to (3) are not performed, and the unreacted nickel foam raw material is directly used in step (4).

[0104] Comparative Example 2

[0105] The method is basically the same as Example 1, except that step (4) and step (5) are not performed.

[0106] Test Example 1

[0107] The nickel-based electrocatalyst prepared in Example 1 was activated by a short period of power supply to remove the polymer loosely attached to its surface; the activated nickel-based electrocatalyst was used as a working electrode, and a 5% potassium hydroxide aqueous solution was used as an electrolyte. The potential range was 1.0 V to 2.0 V, and the temperature was 5 mV s -1 The scan rate was 10 mA cm-3 using linear sweep voltammetry and an electrochemical workstation. -2 The voltage required for the OER process is Figure 3 shown.

[0108] Depend on Figure 3 It can be seen that when the nickel-based material prepared in Example 1 is used as an OER electrocatalyst, it reaches 10 mA cm -2 The voltage required for the current density is 1.41 V, which is much lower than the voltage of 1.79 V of nickel foam. Moreover, compared with the theoretical decomposition voltage of OER of 1.23 V, the overpotential is no more than 0.18 V. This shows that the nickel-based electrocatalyst prepared in Example 1 can be fully applied to electrochemical alkaline water hydrogen production, and can significantly improve the reaction efficiency and reduce energy consumption.

[0109] Table 1 also records the results of the nickel-based materials prepared in Examples 1 to 9 and Comparative Examples 1 to 2 as OER electrocatalysts under the same test conditions. -2 The voltage value required for the current density.

[0110] Table 1

[0111]

[0112]

[0113] Test Example 2

[0114] After a short period of power activation, the loose polymer attached to the surface of Example 1 was removed; the activated nickel-based electrocatalyst was used as the positive electrode and negative electrode of the electrolytic cell, respectively, and a 5% potassium hydroxide aqueous solution was used as the electrolyte. The electrolysis was continuously carried out for 40 hours at a constant cell voltage of 1.65V, and the current density-time curve test was performed. The results are as follows Figure 4 shown.

[0115] like Figure 4 As shown in the figure, during the electrocatalytic water splitting reaction, the nickel-based electrocatalyst prepared in Example 1 and the nickel foam used for comparison both showed good stability, but the holding current and residual current of the nickel foam were both low. After the nickel-based electrocatalyst prepared in Example 1 was electrolyzed at a constant cell voltage of 1.65 V for 40 h, the residual current reached 45.0 mA cm -2 Compared with 0.5h, the current density fluctuation value is as low as 5.7mA cm -2 .

[0116] Table 2 below also records the residual current values ​​of the nickel-based electrocatalysts prepared in Examples 1 to 9 and Comparative Examples 1 to 2 after 40 hours of electrolysis testing at a constant cell voltage of 1.65 V under the same test conditions.

[0117] Table 2

[0118]

[0119]

[0120] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A nickel-based electrocatalyst, characterized in that The nickel-based electrocatalyst comprises a nickel substrate, a sulfide layer, a sulfonate layer and a capping layer from inside to outside; The sulfonated layer includes a sulfonic acid group, and the capping layer includes at least one of an aniline group, a pyrrolyl group or a thiophene group.

2. The nickel-based electrocatalyst according to claim 1, characterized in that The nickel substrate includes at least one of a nickel sheet, a nickel alloy sheet, nickel foam or a nickel wire mesh.

3. The method for preparing a nickel-based electrocatalyst according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: Step 1, preparation of sulfonation layer: placing the nickel substrate in a sulfur-containing alkaline solution for pre-sulfurization, and then adding nickel sulfate and a dispersant for sealing reaction to obtain a sulfided nickel substrate; fully mixing the sulfided nickel substrate with a sulfonation reagent, and after reaction, obtaining a nickel substrate with a sulfonation layer on the surface; Step 2, preparation of the end-capping layer: the nickel substrate with the sulfonated layer on the surface is fully mixed with the end-capping agent and the oxidative polymerization agent in sequence, and after the reaction, a nickel-based electrocatalyst with the end-capping layer fixed on the surface is obtained.

4. The method for preparing a nickel-based electrocatalyst according to claim 3, characterized in that: The sulfur-containing alkali solution comprises sulfur powder and alkali solution, and the solid-liquid ratio of the sulfur powder to the alkali solution is 1g: (20-40)mL; Preferably, the pH of the alkali solution is ≥10; Preferably, the pre-vulcanization time is 0.2h to 1h.

5. The method for preparing a nickel-based electrocatalyst according to claim 3, characterized in that: The temperature of the sealing reaction is 140°C to 180°C, and the time of the sealing reaction is 5h to 20h; Preferably, the dispersant comprises at least one of polyvinyl pyrrolidone, polyvinyl alcohol, methyl cellulose, and carboxymethyl cellulose; Preferably, the mass ratio of the nickel sulfate to the dispersant is 1:(0.5-1.5).

6. The method for preparing a nickel-based electrocatalyst according to claim 3, characterized in that: The sulfonating agent is an organic sulfonic acid or an organic sulfonate, and the sulfonating agent includes at least one of p-toluenesulfonic acid, p-ethylbenzenesulfonic acid, dodecylsulfonic acid, dodecylbenzenesulfonic acid, sodium p-toluenesulfonate, sodium p-ethylbenzenesulfonate, sodium dodecylsulfonate, sodium dodecylbenzenesulfonate, potassium p-toluenesulfonate, potassium p-ethylbenzenesulfonate, potassium dodecylsulfonate or potassium dodecylbenzenesulfonate; Preferably, every 1m 2 The amount of the sulfonating agent used in the nickel substrate with a surface area of ​​0.05 mmol to 0.15 mmol; Preferably, the mixing reaction time of the sulfonation reagent and the sulfided nickel substrate is 0.2 h to 1 h.

7. The method for preparing a nickel-based electrocatalyst according to claim 3, characterized in that: The end-capping agent includes at least one of aniline, pyrrole or thiophene; Preferably, the molar ratio of the end-capping agent to the sulfonating agent is (1-4):1; Preferably, after adding the end-capping agent, the mixture is mixed and reacted for 0.2 h to 1 h, and then the oxidative polymerization agent is added.

8. The method for preparing a nickel-based electrocatalyst according to claim 3, characterized in that: The oxidative polymerization agent includes at least one of ammonium persulfate, ferric chloride, chloroplatinic acid or hydrogen peroxide; Preferably, the molar ratio of the oxidative polymerization agent to the end-capping agent is (0.5-2):1; Preferably, after adding the oxidative polymerization reagent, the mixture is mixed and reacted for 1 h to 10 h to obtain the nickel-based electrocatalyst.

9. A water electrolysis electrode, characterized in that: Comprising the nickel-based electrocatalyst as claimed in claim 1 or 2.

10. A method for electrolyzing water, characterized in that: Electrolyzing the electrolyte using an electrode connected to a power source, wherein the electrode comprises the water electrolysis electrode as claimed in claim 9, and the electrolyte is an alkaline aqueous solution; Preferably, the alkaline aqueous solution comprises one or both of a sodium hydroxide solution and a potassium hydroxide solution, and the mass concentration of the alkaline solute in the alkaline aqueous solution is 10% to 30%; Preferably, the voltage of the power supply is a constant voltage or an alternating voltage, and the voltage is ≥1.41V.